Pengenalan E-LKPD Terintegrasi Pendekatan Multimodal: Strategi Praktis Pendorong Keterlibatan Peserta Didik SMAN 1 Mataram - Amrullah, Lalu Azikri; M Fauzi Muhajir; Muh. Makhrus (Indonesian Publication Center, 2025)
Physics learning, especially for abstract material such as momentum and impulse, often faces challenges related to the limitations of conventional teaching media that hinder in-depth exploration and active student participation. This practical research aims to describe the practical strategy of introducing a Multimodal Approach Integrated E-Student Worksheet (e-LKPD) and analyze its potential as a driver of student engagement at SMAN 1 Mataram. The method applied was a practice-based approach, integrated with the Problem Based Learning (PBL) model, conducted through stages of Preparation, Implementation, and Practical Reflection on students of Class XI IPA 1. Observational results indicate that the activity ran smoothly and received a very positive response. The Multimodal e-LKPD, with the integration of features such as PhET Interactive Simulation, contextual videos, and text and infographics, proved to be an effective strategy serving as a strong catalyst for active participation. This was evident from the increased enthusiasm and student initiative to attempt experimental scenarios beyond the guidelines. In conclusion, this e-LKPD successfully transformed static teaching media into a trigger for curiosity and support for self-directed learning, proving its role as a superior contextual solution in line with the demands of the Merdeka Curriculum.